2010
DOI: 10.1128/jvi.00312-10
|View full text |Cite
|
Sign up to set email alerts
|

Sequence Variability in Clinical and Laboratory Isolates of Herpes Simplex Virus 1 Reveals New Mutations

Abstract: Herpes simplex virus 1 (HSV-1) is a well-adapted human pathogen that can invade the peripheral nervous system and persist there as a lifelong latent infection. Despite their ubiquity, only one natural isolate of HSV-1 (strain 17) has been sequenced. Using Illumina high-throughput sequencing of viral DNA, we obtained the genome sequences of both a laboratory strain (F) and a low-passage clinical isolate (H129). These data demonstrated the extent of interstrain variation across the entire genome of HSV-1 in both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
172
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(176 citation statements)
references
References 85 publications
3
172
1
Order By: Relevance
“…Both genes also exhibit some variation in other HSV-1 strains. Compared to strain 17, the deduced US8A proteins of the clinical isolate H129 and of strain HF10 exhibit one and four amino acid substitutions, respectively (McGeoch et al, 1985;Szpara et al, 2010;Ushijima et al, 2007). Likewise, the US9 proteins of HSV-1 strains 17 and HF10, and of isolate H129 differ at one or two positions.…”
Section: Us9 and Us8a Mutations In Hsv-1 Kosmentioning
confidence: 99%
“…Both genes also exhibit some variation in other HSV-1 strains. Compared to strain 17, the deduced US8A proteins of the clinical isolate H129 and of strain HF10 exhibit one and four amino acid substitutions, respectively (McGeoch et al, 1985;Szpara et al, 2010;Ushijima et al, 2007). Likewise, the US9 proteins of HSV-1 strains 17 and HF10, and of isolate H129 differ at one or two positions.…”
Section: Us9 and Us8a Mutations In Hsv-1 Kosmentioning
confidence: 99%
“…The complete genome of the HSV-1 laboratory strain 17 was determined in 1988 (5), and a large panel of HSV-1 genomes was recently sequenced (6,7). Analysis of this large panel of HSV-1 genomes from several geographically distinct regions (6) has shown that despite high levels of sequence conservation, HSV-1 strains exhibit interstrain diversity, as well as geographic clustering (6).…”
mentioning
confidence: 99%
“…The TK mutation observed occurred in eight clones, suggesting that it might provide some selective advantage in the course of the transfers in 143 TK 2 cells (Table 1). The HSV-1 genomic regions (belonging to the polymerase, glycoprotein gD and thymidine kinase genes) used to sample the presence of mutations in HSV-1 clones, were chosen because they represent structural and non-structural, as well as dispensable and essential genes (McGeoch et al, 2008;Roizman et al, 2007;Szpara et al, 2010). They should mirror the entire HSV-1 genome in terms of point mutation acquisition because in a comparison of strains 17, H129 and F, mutations were distributed along the entire coding-region, and the number of substitutions in the DNA polymerase, glycoprotein D and thymidine kinase did not differ significantly from the average for all encoded proteins (Szpara et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…1 ). Considering that the HSV-1 genome has 152 400 bp (Szpara et al, 2010), and assuming that the number of mutations found reflects the average number of mutations per genome, the HSV-1 clones subjected to multiple plaque-to-plaque transfers accumulated an average of 54.62 mutations per genome (confidence interval 99 %: 20.31-116.86). Since the average number of transfers undergone by the 23 HSV-1 clones that have been analysed by nucleotide sequencing is 9.6 ( Fig.…”
Section: Mutation Frequencies In Different Hsv-1 Genomic Regionsmentioning
confidence: 99%
See 1 more Smart Citation